(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The article analyzes the differences between genres in English and Uzbek literature is mainly influenced by cultural, historical and linguistic factors based on foreign sources. This article includes several uzbek authors’ works.